El valor de la cartera de clientes de empresas de telecomunicaciones en México (The value of customer portfolio for telecommunication companies in Mexico) - Saldaña, J.; Palomo, M. (Facultad de Contaduría Pública y Administración U.A.N.L., 2006)
Abstract. The purpose of this study is to determine which customers are more profitable. Companies must consider the income their customers generate, as well as the costs of acquiring and keeping them. However the analysis can’t end there, companies are well aware that, although customers´ past performance could be helpful to asses their future performance, it could also be tricky. Companies have started to pay attention to the unpredictable customers´ behavior, therefore, analyzing customers´ long term value, or even customers´ life time value (LTV). Nevertheless, only few companies have bothered to evaluate if their desirable individual customers are, from the risk stand point, are desirable collective customers based on the customers´ value change. The value of each customer changes to reflect the identity of the group it belongs to, as well as to reflect in advance, the effect it will have on it´s group. This analysis has been designed to obtain the correlation between the risk-return rate of a customer and a general portfolio as the result of customer´s contribution to the LTV of such portfolio in telecommunication companies. Resumen. Con el fin de determinar qué clientes serán más rentables, un negocio debe considerar en primer lugar los ingresos que éstos han estado generando y cuánto costará adquirirlos y mantenerlos. Pero el análisis no se puede detener ahí, las empresas son conscientes de que el desempeño pasado, si bien resulta útil para hacer predicciones, puede ser muy engañoso. Las empresas han comenzado a tratar el problema del comportamiento impredecible de los clientes. Los negocios se han dedicado al análisis del valor a largo plazo, o incluso el valor vitalicio del cliente individual, pero muy pocas se han molestado en evaluar si todos sus clientes individuales deseables son, desde el punto de vista del riesgo, deseables colectivamente. Puesto que el valor de un cliente cambia para reflejar tanto la identidad del grupo al que se suma como el efecto anticipado en la predictibilidad del mismo. Este análisis esta diseñado para captar la correlación entre la tasa riesgo-retorno del cliente y la de la cartera general teniendo como resultado la contribución al valor vitalicio al riesgo de una cartera de clientes de empresas de telecomunicaciones.